DFT supported experimental investigation of strain induced interfacial modification in Au-Ag bimetallic nanoparticles coated on activated sand - Kriti Bijalwan; Pankaj Kandwal; Jyoti Rawat; Aditi Kainthola; Mohit Sharma; Himani Sharma; Archana Mishra; Charu Dwivedi (Applied Surface Science Advances, 2022)
In this study, the strain induced modification in Au-Ag bimetallic nanoparticles (BNPs) coated on silica rich activated sand has been investigated. The coating of BNPs on activated sand modifies the interface as well as induces microstrain in the structure of the BNPs. The detailed investigation of the interfacial interaction of BNPs with silica in activated sand is performed by using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and micro-Raman spectroscopy. Phonon confinement model has been employed to find out the insights of the Raman spectrum. The effect of microstrain induced in the nanoparticles is found to be influencing the catalytic efficiency significantly. The effectiveness as well as the kinetics and thermodynamics of the BNPs coated on activated sand has been studied for the catalytic reduction of an aromatic nitro compound usually present in wastewater. Density functional theory has also thrown light on the enhanced photocatalytic activity of the BNPs supported on activated sand and provides finer details of the electronic structure. Also, the supported BNPs can be conveniently recovered and reutilized multiple times without significant reduction in the catalytic efficiency.